"I'm using cigarettes to quit JUUL": An analysis of Twitter posts about JUUL cessation. (December 2020) - Unger, Jennifer B.; Rogers, Christopher; Barrington-Trimis, Jessica; Majmundar, Anuja; Sussman, Steve; Allem, Jon-Patrick; Soto, Daniel W.; Cruz, Tess Boley
Highlights: JUUL users posted about quitting JUUL on Twitter. Themes included quit methods, have quit, want to quit, reasons to quit, difficulty. Twitter users reported numerous unsuccessful quit attempts. Twitter users joked about switching to more harmful substances to quit Juul. Abstract: Introduction: JUUL, a small pod-based vaping device that aerosolizes nicotine salts, is popular among adolescents and young adults. Because of JUUL's high nicotine content, JUUL users can become nicotine dependent very quickly and have difficulty quitting. Nicotine-dependent JUUL users might turn to Twitter to seek advice, share their cessation struggles, or report their success rather than confiding in friends or family. Method: This study analyzed Twitter tweets (N = 3192) posted in 2018–2019 to identify common themes about quitting JUUL. Tweets containing the keywords "JUUL" and "quit" or "quitting" were analyzed qualitatively and grouped into themes. Results: The most common themes were Methods to quit (25.4%), Have quit (17.8%), Want to quit (16.1%), Reasons to quit (9.6%), Difficulty quitting (7.9%), Barriers to quitting (2.9%), and Curious about quitting (2.1%). Methods to quit included evidence-based tobacco cessation methods such as nicotine replacement therapy and enrolling in a text-to-quit program, but they also included non-evidence-based strategies such as buying lower-nicotine pods online or switching to other tobacco products including cigarettes. Former JUUL users who had quit successfully generally expressed pride but also acknowledged that quitting was very difficult. Reasons for quitting included adverse health effects such as breathing problems and the financial cost of a JUUL habit. Posters mentioned their extreme difficulty quitting JUUL, numerous failed quit attempts, and numerous barriers to quitting including intense physical and emotional withdrawal symptoms. Some posters joked about switching to cigarettes or other drugs to quit JUUL. Conclusion: Results indicate that JUUL cessation is difficult and that some JUUL users want to quit. Health communication messages are needed to direct JUUL users to effective cessation strategies.